Partisipasi Politik Pemilih Disabilitas di Kecamatan Baregbeg Kabupaten Ciamis pada Pilkada Serentak Tahun 2024 - Andi Sunardi; Arie Budiawan; Rindu Garvera (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Regional Head Elections (Pilkada) are crucial for upholding popular sovereignty and realizing democracy. This research aimed to examine the level of political participation among voters with disabilities and the factors contributing to their low engagement in the 2024 Pilkada in Baregbeg District. The research method used was qualitative with a descriptive approach, involving field studies, literature reviews, and data analysis. The results showed that while the 2024 Pilkada in Baregbeg District, Ciamis Regency, was successfully executed, the participation of voters with disabilities was very low, at only 29.93% of the 294 registered voters. This low participation was caused by external micro factors such as non-inclusive socialization (lack of assistive tools), suboptimal voter education, budget limitations, ineffective 'jemput bola' mechanisms, insufficient family support, unfriendly polling station locations, and minimal initiatives from stakeholders and disability organizations. Additionally, internal macro factors of disabled individuals also played a role, including communication limitations (for those with hearing, visual, speech, and intellectual impairments), differences in information access and mobility, varying levels of understanding, low organizational awareness, and limited scope of movement and social interaction. The socialization efforts already undertaken have not been able to significantly increase participation, indicating the need for a more comprehensive and inclusive approach.